Past and present thermokarst lake dynamics in the Yedoma Ice Complex region of North-Eastern Yakutia - Veremeeva, Alexandra; Günther, Frank; Nitze, Ingmar; Grosse, Guido; Glushkova, Nadezhda; Rivkina, Elizaveta (Laboratoire EDYTEM - UMR5204, Université Savoie Mont Blanc, Bâtiment «Pôle Montagne», 2018)
Thermokarst lakes are typical components of the yedoma-alas dominated relief in the coastal lowlands of North- Eastern Yakutia and formed as a result of thawing Late Pleistocene ice-rich Yedoma Ice Complex (IC) deposits. The aim of our study is to estimate thermokarst lake area changes from the early Holocene onwards based on RS data. The decrease of thermokarst lake area from the early Holocene, taking into account total alas depression areas, is as much as 81-83 %. Modern climate warming has led to a general trend of thermokarst lake area decrease. Lake drainage occurs mostly on elevated sites with high Yedoma IC fraction while lake area increase is typical for low-lying areas with a small Yedoma IC fraction. The area increase of thermokarst ponds on flat, boggy yedoma surfaces indicates ice wedge degradation in response to rising summer air temperatures and precipitation.